Women in Islamic Education Management: Learning from Pesantren Practices - Siti Nur Hidayah; Ahmad Arifi (Ulumuna, 2017)
This paper focuses on two issues. Firstly, the role performed by women (nyais) in managing pesantren by considering the issue of work division, authority and responsibility principles in management practices. Secondly, it observes on how knowledge is managed and preserved in pesantren. This paper is based on reviews of the previous research about women and pesantren. Thi study shows that there are three types of nyai’s role in managing pesantren education. First, a nyai who hold clear responsibility, work division and at the same time owned authority in managing a male and female students. Second, a nyai who has a clear division of work, and responsibility but does not have authority in managing a male and female students. And third, a nyai who leads a sepcific female pesantren and hold authority, responsibility and task in developing her pesantren. It is through various method of learning, espceially memorization of knowledge and the Qur’an, that tradition and knowledge of Islamic tradional subjects in pesantren are preserved and practiced.